A Qualitative Study on Coping Strategies of Chinese Women With Metastatic Breast Cancer Undergoing Chemotherapy - Guo, Yi-Qiang; Ju, Qing-Mei; You, Miaoning; Yusuf, Azlina; Wu, Ying; Soon, Lean Keng (Frontiers in Psychology, 2022)
Purpose: Women with breast cancer undergoing chemotherapy (CT) often describe low levels of coping strategy. The present study explores the qualitative experience of coping strategies for women with metastatic breast cancer (MBC) undergoing CT in Beijing. Methods: Twenty Chinese MBC women undergoing chemotherapy participated in semi-structured interviews to explore different aspects of coping strategies. In addition, a qualitative approach using thematic analysis was followed. Results: Three themes are highlighted: (a) Maintaining hope; (b) Spiritual growth; and (c) Self-perceived support resources. Conclusions: The present study results have led to a greater understanding of the tremendous impact of CT on MBC women’s lives. This research provides insight into the scope of maintaining hope. Spiritual growth and self-perceived support resources were crucial factors to coping strategies among MBC women to improve their quality of life. Clinical Relevance: By attaining the adaptive coping strategies and further understanding about Chinese MBC women, health care professionals are encouraged to appraise MBC women’s specific problems and adopt effective interventions to improve MBC women’s psychosocial wellbeing.